2006
DOI: 10.1016/j.amjhyper.2005.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension Is Associated With Insulin Resistance State and Not With an Initial Renal Function ImpairmentA Metabolic Syndrome in Active Subjects in Spain (MESYAS) Registry Substudy

Abstract: Background:The aim of this study was to assess the prevalence of metabolic syndrome (MS) and other surrogate markers of insulin resistance, and whether these markers are better for defining the prehypertensive state than is renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 37 publications
8
47
1
6
Order By: Relevance
“…Many papers found the association between insulin resistance and prehypertension 8,38,39 or hypertension 40 . Hyperinsulinemia directly increases sodium re-absorption in renal tubules and may lead to fluid retention 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many papers found the association between insulin resistance and prehypertension 8,38,39 or hypertension 40 . Hyperinsulinemia directly increases sodium re-absorption in renal tubules and may lead to fluid retention 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Many cross-sectional studies of different populations demonstrated that prehypertensive individuals had higher total cholesterol, LDL-C, TG and lower HDL-C than normotensive subjects [6][7][8][20][21][22][23][24][25][26][27][28][29][30] . Some prospective studies also showed that dyslipidemia could predict occurrence of incident hypertension by years [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is in line with recent clinical studies in which prehypertension was associated with higher prevalence of metabolic syndrome compared with normotensive status. 25 Psychological stress is another factor potentially involved in the progression of carotid IMT, 26 and hyperactivity to stressful stimuli has been described in WCHs. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Less attention has been paid to the determining factors of prehypertension. Body mass index (BMI or waist girth as determinants of prehypertension was found to be modulated by gender (3), insulin resistance was reported to be associated with prehypertension in a Spanish cohort (4), and ethnic differences among Americans were shown to play a role in the populationattributable risk of prehypertension (5). Adiposity and triglycerides were consistently higher from childhood through adulthood in prehypertensive subjects (6).…”
Section: Introductionmentioning
confidence: 99%